Tospoviruses in the Republic of Macedonia during 1996-2010, occurrence and distribution - Rusevski, Rade; Kuzmanovska, Biljana; Bandzo, Katerina; Risteski, Mihajlo; Sotirovski, Kiril (Bulgarian Journal of Agricultural Science, 2013)
The research was carried out during the period between 1996 and 2010. The presence of two tospoviruses (TS WV and INSV) in the Republic of Macedonia was confirmed by different serological tests and characterization based on the size of N proteins obtained from different viral isolates. The results showed that the dominant tospovirus in Macedonia is TSWV, with the exception of the sample GV-I, in which the presence of INSV was detected for the first time in the Republic of Macedonia.
Keywords: tospoviruses, TSWV, INSV